Organizational and socio-psychological mechanisms for making managerial decisions in conflict situations between adolescents - Mamayusupova Iroda Khamidovna (International Journal on Orange Technologies, 2021)
This article explores conflicts between various formal or informal groups. Conflicts are general stages of origin, regardless of their specificity and different spheres. " Conflicts of interests, interests, goals, positions, opinions, views of the opposite direction, an intensified conflict